A Viable Architecture for the Integration of a Recommender System and Mobile Solution for the Management of HIV/AIDS - Afolabi, Adekunle Oluseyi (Journal of Health Informatics in Africa, 2018)
Background and Purpose: Mobile devices are a common sight everywhere in the world with attendant phenomenal growth in various ways. As a result of their mobility, there has been an increase in penetration among different cadres of people regardless of their social or economic status in the society, thus bringing about changes in the ways businesses are done in commerce, economic and health sectors. Recommender systems in medical and healthcare context are emerging significantly with attendant positive impacts on the speed and accuracy of diagnosis. A few successful implementation of such recommender systems alongside few with good results have been highlighted in literature. However, HIV/AIDS have also become endemic in most developing countries with victims being afraid to openly seek medical care because of stigmatization. As a result of mobility and a degree of privacy that mobile devices ensure combined with the ability of recommender systems, interactive solution is desirably helpful in providing care for infected individuals, who especially are reluctant to seek medical care due to stigma. survey conducted on the potential of mobile phones for counselling HIV/AIDS patients shows over 80% comfortable discussing health issues (including HIV status) via mobile phone before face-to-face contact. This is an indication that mobile devices have the ability to play a vital role in HIV/AIDS patients’ management. A further analysis of the survey revealed key attributes of a desirable architecture and these have served as a basis for developing the architecture presented in this paper. Methods: Questionnaire was used to gather information from potential users who are drawn from the group susceptible to the malaise, 250 youth and health workers from the ages of 18-50. Respondents were drawn from students in a university in Osun State Nigeria and health workers in a nearby hospital. The result was further analyzed and key attributes were extracted with a view to identifying relevant components for the proposed architecture. Results: survey conducted on the potential of mobile phones for counselling HIV/AIDS patients shows over 80% comfortable discussing health issues (including HIV status) via mobile phone before face-to-face contact A further analysis of the survey revealed key attributes of a desirable architecture and these have served as a basis for developing the architecture presented in this paper. Conclusions: It can be seen from the result of the survey, its further analysis and the presented architecture that mobile devices have a role to play in the management of HIV/AIDS, and is more effective when integrated with dynamic recommender systems.